Analisis Pengendalian Kualitas Produk Keripik Tempe di Batam Menggunakan Pendekatan Metode FMEA dan RCA - Sumantika, Arsyad; Tarigan , Elsya Paskaria Loyda; Prasetyo, Bahariandi Aji (Fakultas Teknik UMRI, 2025)
This study aims to analyze the quality control of tempeh chips products in Batam using the Failure Mode and Effect Analysis (FMEA) and Root Cause Analysis (RCA) approaches. Tempeh chips are processed food products that have significant economic value for MSMEs in Batam, but often face various challenges related to quality control. The research method used is a combined qualitative and quantitative approach with a sample of 3 MSMEs producing tempeh chips in Batam. The results of the study identified several major quality problems in the tempeh chips production process, including non-uniform thickness, damaged packaging, soft texture, imperfect packaging seals, and weight contents that do not match the label. Through the application of FMEA, this study calculates the Risk Priority Number (RPN) for each failure mode, identifying five critical problems with the highest RPN values. Furthermore, using RCA and 5-Why analysis so that the root cause of each problem can be identified based on human, machine, method, material, and environmental factors. Based on the results of the analysis, this study recommends a series of comprehensive quality control recommendations, including the development of Standard Operating Procedures (SOPs), quality monitoring systems, employee training programs, and the implementation of quality control checkpoints. This research provides a significant contribution to the development of the tempeh chips industry in Batam and can be a reference for similar research in other areas.